Colonoscopy Quality Assurance in Ontario: Systematic Review and Clinical Practice Guideline. Issue 5 (2014) - Tinmouth, Jill; Kennedy, Erin B; Baron, David; Burke, Mae; Feinberg, Stanley; Gould, Michael; Baxter, Nancy; Lewis, Nancy
Abstract : Colonoscopy is fundamental to the diagnosis and management of digestive diseases and plays a key role in colorectal cancer (CRC) screening and diagnosis. Therefore, it is important to ensure that colonoscopy is of high quality. The present guidance document updates the evidence and recommendations in Cancer Care Ontario's 2007 Colonoscopy Standards, and was conducted under the aegis of the Program in Evidence-Based Care. It is intended to support quality improvement for colonoscopies for all indications, including follow-up to a positive fecal occult blood test, screening for individuals who have a family history of CRC and those at average risk, investigation for symptomatic patients, and surveillance of those with a history of adenomatous polyps or CRC. A systematic review was performed to evaluate the existing evidence concerning the following three key aspects of colonoscopy: physician endoscopist training and maintenance of competency; institutional quality assurance parameters; and colonoscopy quality indicators and auditable outcomes. Where appropriate, indicators were designated quality indicators (where there was sufficient evidence to recommend a specific target) and auditable outcomes (insufficient evidence to recommend a specific target, but which should be monitored for quality assurance purposes). The guidance document may be used to support colonoscopy quality assurance programs to improve the quality of colonoscopy regardless of indication. Improvements in colonoscopy quality are anticipated to improve important outcomes in digestive diseases, such as reduction of the incidence of and mortality from CRC.